2019
DOI: 10.18621/eurj.533569
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of patiens with brain death

Abstract: Objectives: We aimed to retrospectively analyze brain death cases in the our intensive care units. Methods: We examined archive records of brain death cases diagnosed between January 01, 2014 and October 01, 2018. We recorded patients' demographics (age, gender, place of birth, blood type and diagnosis on admission), time to the preparation of the report, additional tests performed, rate of organ donation, donor rate, and number of organs removed. Results: A total of 151 brain death cases were detected. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The mean age of patients diagnosed with BD varies in the literature, and it is reported to be common in patients aged 40-50 years 14,20 . In our study, the mean age of patients diagnosed with BD was 59.9 years, and this result was similar to the results of other studies conducted in our country 15,19 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The mean age of patients diagnosed with BD varies in the literature, and it is reported to be common in patients aged 40-50 years 14,20 . In our study, the mean age of patients diagnosed with BD was 59.9 years, and this result was similar to the results of other studies conducted in our country 15,19 .…”
Section: Resultssupporting
confidence: 92%
“…In studies conducted in our country, it is seen that the majority of cases diagnosed with BD are male 14,15,19 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In two separate studies conducted in Türkiye between 2008–2019 and 2014–2018, it was determined that approximately 55% of the cases were male and the mean age was 49 and 53, respectively. [ 8 , 9 ] In addition, in the study of Sipahioglu et al [ 10 ] examining the cases diagnosed with 1998 brain death between 2011 and 2019, 63.8% were male and 36.2% were female, and the median age of the cases was 38 years. In the cohort study conducted on 69,735 cases in the USA between 2012 and 2016, 56.47% of the cases were male and 43.53% were female.…”
Section: Discussionmentioning
confidence: 99%
“…The primary disease causing permanent brain death in Türkiye has been identified as approximately 50–55% intracranial haemorrhage. [ 8 , 10 , 15 ] In Spain with 1844 cases and in Italy with 1286 cases, the primary disease causing death was found to be intracranial hemorrhage in 56% and 52%, respectively. [ 16 , 17 ] In the study literature, the primary disease of cases with brain death was found to be hemorrhagic cerebral damage in 47% of cases.…”
Section: Discussionmentioning
confidence: 99%